Molecular analysis of Salmonella paratyphi A from an outbreak in New Delhi, India - Thong, Kwai Lin; Nair, S.; Chaudhry, R.; Seth, P.; Kapil, A.; Kumar, D.; Kapoor, H.; Puthucheary, S.D.; Pang, T. (1998)
In the context of emerging infectious diseases, enteric fever caused by Salmonella paratyphi A deserves increased attention and vigilance, although its severity is often milder than that of S. typhi disease. Outbreaks associated with this organism are exceedingly rare but have recently been reported in India (1) and Thailand. In India, the first reported outbreak of disease associated with S. paratyphi A (1) provided an opportunity to study the molecular epidemiology of infection caused by this organism.